Saccharomyces boulardii CNCM I-745 Modulates the Fecal Bile Acids Metabolism During Antimicrobial Therapy in Healthy Volunteers - Kelly, Ciaran Patrick; Chong Nguyen, Caroline; Palmieri, Lola Jade; Pallav, Kumar; Dowd, Scot E.; Humbert, Lydie; Seksik, Philippe; Bado, Andre; Coffin, Benoit; Rainteau, Dominique; Kabbani, Toufic; Duboc, Henri (Frontiers in Microbiology, 2019)
Saccharomyces boulardii CNCM I-745 (SB) is a probiotic yeast used to lower the incidence of antibiotic-associated Clostridium difficile (C. difficile) infection, though its mechanism of action remains unclear. Cholic acid is a primary bile acid, which triggers the germination and promotes the growth of C. difficile. The intestinal microbiota transforms primary into secondary bile acids. This study examined (1) the antimicrobial-induced alteration of fecal bile acid content, and (2) whether the concomitant administration of SB influences this transformation. This is an ancillary work from a randomized study, which revealed that SB modulates fecal microbiota dysbiosis during antibiotic treatment. Healthy subjects were randomly assigned to (1) SB only, (2) amoxicillin-clavulanate (AC), (3) SB plus AC, or (4) no treatment. We analyzed fecal concentrations of BA by high performance liquid chromatography/tandem mass spectrometry. Compared to the untreated or the SB-treated groups, AC decreased the percentage of fecal secondary BA significantly (days 3 and 7). When SB and AC were administered concomitantly, this decrease in secondary BA was no longer significant. Following treatment with AC, a significant peak of fecal CA was measured on days 3 and 7, which was prevented by the concomitant administration of SB. AC administered to healthy volunteers altered the microbial transformation of primary BA, decreased secondary BA, and increased CA. The latter was prevented by the concomitant administration of SB and AC, suggesting a potent mechanism protection conferred by SB against post-antimicrobial C. difficile infection. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT01473368.